Force Majeure Dan Kebangkrutan Dalam Jangka Pendek: Pembuktian Pada Perusahaan Sektor Perdagangan Yang Terdaftar Di BEI - Ramadona Simbolon; Adek Zuhrati Wardi; Jalilah Ilmiha; Sri Elviani (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
Trading companies are currently really significantly affected by their operational performance so it is possible that trading companies in Indonesia in the era of the - pandemic have experienced a lot of financial distress or have entered a state of bankruptcy. The purpose of this study is to determine the effect of the Covid-19 pandemic on the bankruptcy of trading sector companies listed on the IDX in the short term. This study used 75 companies in the trading sector with observations of conditions before the pandemic and after the pandemic, namely in 2019 and 2020. To predict bankruptcy, the study used a modified Altman Z-Score calculation. Based on the results of the Z-Score calculation, it can be known that the condition of the company is included in the healthy zone, special attention or has the potential to go bankrupt. This research revealed that the Covid-19 pandemic affected the bankruptcy of trading sector companies